Assessment of periodontal abscess among diabetic patients visiting a dental college -a retrospective study - KARPAGAM, G. NITHYA; MALAIAPPAN, SANKARI; PRABU, DINESH (The journal of contemporary issues in business and government, 2020)
Periodontitis is a chronic inflammatory disease characterised by destruction of supporting structures of teeth.Diabetes mellitus is a syndrome of abnormal carbohydrate, fat and protein metabolism that result in acute, chronic complications due to the absolute or lack of insulin.The progression of periodontal disease is influenced by factors like microorganism, host response, systemic background and genetic makeup of the host.1 Chronic hyperglycemia results in production of advanced glycation end substances (AGEs) in the tissues, which have protean effects on the periodontal microenvironment.The aim of the study was to assess the periodontal abscess among diabetic patients visiting dental college. A retrospective data of all the patients reported for periodontal therapy to dental college was collected. The data was extracted from the patients records. Data segregation was done based on age, gender,site of periodontal abscess, blood sugar value probing depth, clinical attachment loss and mobility. After data collection statistical analysis was done in IBM SPSS software version 20. A total 50 diabetic patients with periodontal abscess were evaluated in this study and it showed about 64% of males and 36% % of females with periodontitis had diabetes. The most common age group that was affected was 36-45 years by 36%. The most prevalent site with periodontal abscess is lower left posterior by 24%. Probing depth of 5mm was seen mostly in patients with diabetes and periodontitis (34%). Clinical attachment loss of 6mm was seen mostly in patients with diabetes and periodontitis (50%). Grade 2 mobility was seen predominantly in patients with abscess(48%). Patients with periodontal abscess had blood sugar level above 200mg/dl by 50%. The chi square test was performed to determine the correlation between age of the periodontitis patients and the random blood sugar levels, the P value obtained was 0.045 (p<0.05) statistically significant. The most prevalent age group that was affected with periodontal abscess was between 36-45 years. The males were more affected with periodontal abscess among diabetics. The predominant site involved with periodontal abscess was the lower left posterior region. The association between the blood sugar levels and age was significant statistically.